IINUSAT-1: SATELIT-NANO PERDANA DI INDONESIA UNTUK PENELITIAN DAN PENDIDIKAN - Tri Kuntoro Priyambodo; Agfianto Eko Putra; Muh. Asvial; Ridanto Eko Putro; Gamantyo Gamantyo; Endra Pitowarno; Son Kuswadi; Gunawan S Prabowo (Universitas Trunojoyo Madura, 2011)
Mastery of aerospace technology becomes very important for Indonesia. Due to the given the vast areas of Indonesia mostly in the form of marine waters.This condition has made a guarding and monitoring becomes easy. Therefore needed satellite technology that can be utilized to guard the interests of the territory of Indonesia.The success of developing IiNUSAT-1 on the one hand proves that the universities in Indonesia have competence in the field of nano-satellite development, on the other hand also shows that gotong-royong (working-together) in research-networks and technology will accelerate the research competence. In the first year of development IiNUSAT-1 produced a document Prelimidary Design Review, and a prototype of the nano-satellite. The result shows that the nano-satellite prototype has maximum transfer rate 115.2 kbps and every parameter is sampled every second. Having experience developing and operating the nano-satellite in the first year research project, it will trigger the research related to security and prosperity of the nation. The next version of the nano-satellite will be payloaded with sensors and instruments which can be utilized for national security and prosperity.